Cognitive Therapy and the Punctual Self: Using an Ascetical Framework to Critique Approaches to Psychotherapy - Stewart-Sicking, Joseph (Pastoral psychology, 2015)
Theological examinations of counseling and psychotherapy have typically focused on theory rather than practice. The current study takes a different perspective by studying the implications of cognitive behavioral therapy interventions through the lens of Michel Foucault's framework of technologies of the self. In this analysis, the fundamental exercises of care for the self in Beck's cognitive therapy are identified along with the characteristics of the self that these exercises presume. The results of this analysis show a close correspondence between cognitive behavioral therapy (CBT) and the punctual self identified by Charles Taylor in his studies of modernity. Three aspects of CBT-distancing reflection, thought replacement, and self-mathesis- are identified as potential barriers to integrating spirituality through this therapy, thus pinpointing the practices that lead to the criticisms of perfectionism and naturalism that theoretical studies have identified. These results suggest the utility of a practice-centered approach to critiquing psychotherapy and also call for more research using social science methods to determine how to implement these critiques in practice.